2003
DOI: 10.1021/jo026914g
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies toward Sarain A. Formation of the Western Macrocyclic Ring

Abstract: Starting with the tricyclic core 2b, annulation to form the 13-membered western ring of sarain A has been achieved to afford the macrocycle 30a by initial construction of the sterically congested quaternary center at C-3, followed by elaboration of the C-3 side-chain and ring-closing olefin metathesis. Also included is a parallel conversion of tricycle 2c to macrocycle 30b containing a functionalized side-chain at N-1 suitable for attachment of the eastern macrocyclic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The combined organic extracts were washed with brine, dried (Na2SO4), filtered, and evaporated under reduced pressure. The residue that resulted was purified by preparative TLC on silica gel (CHCl 3/MeOH ) 9:1) to provide 45 (21.6 mg, 90%): [R]D ) +24.8 (c 1.75, MeOH); FTIR 3372, 2915, 1618, 1489, 1459, 1262, 1227, 1077 cm -1 ; 1 H NMR (300 MHz, CDCl3) δ 1.53 (m, 1 H), 1.67 (d, J ) 6.8 Hz, 3 H), 1.75 (d, J ) 11.9 Hz, 1H), 2.18 (dd, J ) 11.9, 4.5 Hz, 1 H), 2.65 (s, 3 H), 2.81 (d, J ) 4.2 Hz, 1 H), 2.93 (m, 2 H), 3.42 (d, J ) 6.7 Hz, 1 H), 3.44 (m, 1 H), 3.54 (m, 1 H), 3.57 (t, J ) 2.2 Hz, 1 H), 3.63 (d, J ) 10.2 Hz, 1 H), 3.74 (dd, J ) 9.7, 5.1 Hz, 1 H), 3.82 (s, 3 H), 4.07 (s, 1 H), 5.37 (q, J ) 6.8 Hz, 1 H), 6.32 (d, J ) 2.1 Hz, 1 H), 6.40 (dd, J ) 8.0, 2.2 Hz, 1 H), 7.01 (d, J ) 8.0 Hz, 1 H); 13 C NMR (75.5 MHz, CDCl3) δ 13.0, 22.6, 28 Preparation of Na-Boc-vellosimine (47). To a solution of vellosimine 46 (100 mg, 0.34 mmol) and Boc2O (100 mg, 0.47 mmol) in dry CH3CN (1 mL) was added DMAP (5 mg).…”
Section: Preparation Of (+)-(2r17s19e)-1920-didehydro-17hydroxy-1-dem...mentioning
confidence: 99%
See 1 more Smart Citation
“…The combined organic extracts were washed with brine, dried (Na2SO4), filtered, and evaporated under reduced pressure. The residue that resulted was purified by preparative TLC on silica gel (CHCl 3/MeOH ) 9:1) to provide 45 (21.6 mg, 90%): [R]D ) +24.8 (c 1.75, MeOH); FTIR 3372, 2915, 1618, 1489, 1459, 1262, 1227, 1077 cm -1 ; 1 H NMR (300 MHz, CDCl3) δ 1.53 (m, 1 H), 1.67 (d, J ) 6.8 Hz, 3 H), 1.75 (d, J ) 11.9 Hz, 1H), 2.18 (dd, J ) 11.9, 4.5 Hz, 1 H), 2.65 (s, 3 H), 2.81 (d, J ) 4.2 Hz, 1 H), 2.93 (m, 2 H), 3.42 (d, J ) 6.7 Hz, 1 H), 3.44 (m, 1 H), 3.54 (m, 1 H), 3.57 (t, J ) 2.2 Hz, 1 H), 3.63 (d, J ) 10.2 Hz, 1 H), 3.74 (dd, J ) 9.7, 5.1 Hz, 1 H), 3.82 (s, 3 H), 4.07 (s, 1 H), 5.37 (q, J ) 6.8 Hz, 1 H), 6.32 (d, J ) 2.1 Hz, 1 H), 6.40 (dd, J ) 8.0, 2.2 Hz, 1 H), 7.01 (d, J ) 8.0 Hz, 1 H); 13 C NMR (75.5 MHz, CDCl3) δ 13.0, 22.6, 28 Preparation of Na-Boc-vellosimine (47). To a solution of vellosimine 46 (100 mg, 0.34 mmol) and Boc2O (100 mg, 0.47 mmol) in dry CH3CN (1 mL) was added DMAP (5 mg).…”
Section: Preparation Of (+)-(2r17s19e)-1920-didehydro-17hydroxy-1-dem...mentioning
confidence: 99%
“…The combined organic extracts were washed with brine, dried (Na2SO4), filtered, and evaporated under reduced pressure. The residue that resulted was purified by preparative TLC on silica gel (CHCl 3/MeOH ) 9:1) to provide authentic diol 53 as a pale yellow powder (4.2 mg, 82%): [R]D ) +60.6 (c 0.165, MeOH); FTIR 3326, 2922, 1608, 1456 cm -1 ; 1 H NMR (300 MHz, CDCl3) δ 1.53 (dd, J ) 9.9, 4.1 Hz, 1 H), 1.71 (d, J ) 6.8 Hz, 3 H), 1.75 (m, 1 H), 2.48 (m, 1 H), 2.53 (d, J ) 7.0 Hz, 1 H), 2.74 (d, J ) 4.6 Hz, 1 H), 3.01 (d, J ) 4.7 Hz, 1 H), 3.46 (m, 2 H), 3.55 (m, 1 H), 3.67 (m, 2 H), 3.92 (d, J ) 5.0 Hz, 1 H), 4.30 (s, 1 H), 5.41 (q, J ) 6.8 Hz, 1 H), 6.83 (m, 2 H), 7.16 (m, 2 H); 13 C NMR (75.5 MHz, CDCl3) δ 12.9, 21.9, 28 (20 mL), and cold 10% aq NH4OH was added to bring the pH to 8. The organic layer was diluted with CH2-Cl2 (20 mL), washed with brine (2 × 20 mL), dried (Na2SO4), filtered, and concentrated under reduced pressure.…”
Section: Preparation Of (+)-(2r17s19e)-1920-didehydro-17hydroxy-1-dem...mentioning
confidence: 99%
“…More recently, the Overman group has devised a novel approach for the enantioselective synthesis of the sarain core. Moreover, Cha has published a nice strategy for construction of the tricyclic core of the sarains via a key 3-oxidopyridinium betaine/cyclopentadiene cycloaddition. In 2005, biogenetically patterned studies leading to the sarain core were reported by Marazano and co-workers .…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress towards sarain A ( 1 ) has been registered by Weinreb,6 Heathcock,7 Cha,8 and Marazano,9 in addition to us 10. Although successful preparations of the diazatricycloundecane core and the saturated macrocycle of 1 have been described,7d, 6c, 8b,c assembly of the highly functionalized 14‐membered ring has been reported only in a simple model system 11. Likewise, chemistry associated with the introduction of the proximal tertiary amine and aldehyde groups has not been described.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent conversion of tetracyclic aldehyde 9 into diene 10 allows the saturated macrocycle to be formed by ring‐closing metathesis followed by hydrogenation 6c. 8b, 14 Using this synthetic sequence, tetracyclic diamine diol 11 was prepared on a multigram scale.…”
Section: Methodsmentioning
confidence: 99%